Case Report: Rhizopus arrhizus Rhino-Orbital-Cerebral Mycosis and Lethal Midline Granuloma: Another Fungal Etiological Agent - Li, Dong Ming; Lun, Li De; Ge, Jie; Zhang, Gong Jie; Li, Xin Lun; de Hoog, G. Sybren (Frontiers in Medicine, 2021)
Objective: Both rhino-orbital-cerebral mycosis and lethal midline granuloma (LMG) may result in midline destruction. LMG has now been generally considered as a natural killer/T cell lymphoma, nasal type (ENKTL-NT) with an association of EBV. Fungi have been detected from the diseased tissues now and then but are often considered as lymphoma-associated infections. We previously reported an ENKTL-NT case with Mucor irregularis, which played a causal role in the disease and was involved in the overexpression of Ki67 and CD56 in the mouse experiment. The present study describes a chronic Rhizopus arrhizus infection with immunological parameters that are closely similar to LMG. We aim to explore the relationship of another Mucorales fungus, R. arrhizus, and LMG in a patient and in mice. Methods: Case study and mouse infection modules were designed for our observation. A 35-year-old man with midline face ulcers which was clinically suspected as LMG was selected. Biopsy specimens were sent for lymphoma diagnosis and microbiological detection. The isolated fungus was tested in an ICR mouse model for mycological and histological analyses. Results: Five tissue samples yielded Rhizopus arrhizus. In the pathology, characteristic inflammation, necrosis, and granulation with thin-walled hyphae are observed. Immunohistochemistry showed NK/T cell infiltration (CD3+, CD8+, TIA1+, GZMB+, PRF+, individual CD56+) with hyperplasia (Ki67+) and angioinvasion. The patient recovered completely with amphotericin B. In the murine experiment, R. arrhizus caused angioinvasion with NK/T cell infiltration (CD3+, CD56+, TIA1+, GZMB +, PRF+) with proliferation (Ki67+) and was re-isolated from the infected host. Conclusions: We here describe a mid-face destruction patient, which was diagnosed by the top pathologists in China according to the current criteria of NK/T cell lymphoma, with a negative result for EBV and positive result for R. arrhizus. With a then developed mouse experiment, the R. arrhizus in the diseased lesions was responsible for the NK/T cell infiltration (CD3+, CD8+, CD56+, TIA1+, GZMB+, PRF+), proliferation (Ki67+), and angioinvasion, suggesting another fungal etiological agent for LMG, which could be eradicated with amphotericin B. Limitations: The sample size is not sufficient for statistical analysis. However, our findings are suggestive for the role fungus plays in LMG.